(untitled) (Research, Society and Development, 2021)
Dulce de leche, a dairy dessert highly consumed in Latin American countries, is obtained from the evaporation of water from milk added with sugar. The heat treatment associated with evaporation triggers several chemical changes that directly influence the characteristics of the final product. Despite having few ingredients in its formulation, the final product can present very different characteristics depending on the processing conditions and of the controlled parameters. Therefore, it is evident that knowledge of topics such as the buffering capacity of milk, the use of acidity regulators, Maillard reaction and the main factors that affect its occurrence, rheology and texture, are extremely important in the manufacture of dulce de leche. The purpose of article is to review the main chemical reactions involved in the processing of dulce de leche and relate them to the characteristics obtained in the product.